Menyoal Pandemi dan Vaksinasi dalam Nuansa Nilai Dasar Perjuangan Himpunan Mahasiswa Islam - Muhammad Irsal Basda (STAI DDI Kota Makassar, 2022)
This research aim to know: (1) the pros and cons that occur in the community regarding the Covid-19 pandemic and vaccinations, (2) the role of the NDP provides a perspective in shaping the synergy of the nation amid the pandemic. The research method used in this research is a literature study, the data obtained are compiled, analyzed and then concluded in order to get some conclusions related to the pandemic problem and vaccination in the nuances of the Islamic Student Association Struggle Basic Values. The conclusion obtained from the results of this study is that the NDP is expected to shape and influence the way of thinking and outlook on life of HMI cadres. The NDP has a role in criticizing dogmatic thinking on the issue of the pandemic, questioning various policies that do not lead to the interests of the people, and providing its own ideal perspective through the harmony of faith, knowledge and charity.